Can Miracles Lead to Crises? : The Role of Optimism in Emerging Markets Crises - Boz, Emine (IMF Working Papers; Working Paper, 2007)
Emerging market financial crises are abrupt and dramatic, usually occurring after a period of high output growth, massive capital flows, and a boom in asset markets. This paper develops an equilibrium asset-pricing model with informational frictions in which vulnerability and the crisis itself are consequences of the investor optimism in the period preceding the crisis. The model features two sets of investors, domestic and foreign. Both sets of investors learn from noisy signals, which contain information relevant for asset returns and formulate expectations, or "beliefs," about the state of productivity. We show that, if preceded by a sequence of positive signals, a small, negative noise shock can trigger a sharp downward adjustment in investors' beliefs, asset prices, and consumption. The magnitude of this downward adjustment and sensitivity to negative signals increase with the level of optimism attained prior to the negative signal.